Evaluation of Milk Urea Nitrogen of Dairy Cows Reared Under Different Feed Bases in the Different Seasons (Journal of Science Foundation, 2013)
Ten cows, each of native (local cow) and crossbred (local × crossbred) origins differing in lactation yield were used in 2×2×2×2 factorial experiment using RBD to evaluate existing milk urea nitrogen (MUN) of cows considering regions and seasons. The live weight and BCS of cows under good feed base management condition was higher than of the poor feed base management condition. Feed intake of cows under good and feed base management condition was significantly (P